Internalisasi Dan Implementasi Pendidikan Toleransi Beragama Di Pondok Pesantren Al Ihya Kalirejo Lampung Tengah - Afifudin Ahmad Robbani; Henisa Rosulawati (Jurnal Dinamika Pendidikan Islam, 2025)
This study aims to analyze the process of internalizing tolerance values through the study of classical Islamic texts (kitab kuning), explore the implementation of tolerance in students' religious practices, and identify challenges faced by Al-Ihya Islamic Boarding School Kalirejo Central Lampung in religious tolerance education. Using a qualitative approach with field research methods over six months, data were collected through in-depth interviews, participatory observation, and documentation. Results show that internalization is conducted through systematic study of classical texts emphasizing comparative fiqh and legal methodology (istinbath), involving three stages: transformation, transaction, and transinternalization of values. Implementation is reflected in students' ability to adapt to differences in ritual practices across madhhabs and Islamic organizations, as well as a culture of polite argumentation. Challenges include students' doubts about their future, limited learning motivation, and varying abilities in understanding classical texts. The boarding school proves to play a strategic role in shaping students' inclusive and moderate character as peace agents in plural society.